Proposed Assessment for PT KAI Station Hotel (The Indonesian Journal of Business Administration, 2014)
Abstract- PT. KAI has many premium assets such as land that is used by Perum Damri as pool bus at Jl. Kebun Kawung. PT. KAI plans to build a hotel in this unproductive land since hospitality industry has become an opportunity for the company to gain profit by adding this industry to its business portfolio. Macro economic and hospitality industry conditions are still very promising. Their growths give the possibility to make a good profit. Hotel to be built is a budget business hotel. In addition, the possible risks of this project are also identified and mapped. The risk management helps determine factors that affect the IRR of the hotel to be built.There are several factors to be used to maximize the companyâ€™s return. Such factors, affecting the IRR, are Room Rate Inflation; Capital Structure; Occupancy Rate; Construction Costs; Land Compensation; Room Rate; Interest Rate; and Pre-ConstructionKeyword: Risk Management, Hotel Planning, Sensitivity Analysis, Monte Carlo AnalysisÂ